Contradictions and Confusions in Development Work: Exploring the Realities of Bangladeshi NGOs - Arvidson, Malin (Journal of South Asian development, 2008)
Ambiguous practices and identities of NGOs have become a source of increasing concern for all involved in development intervention. But apart from pointing at dishonest marketing and unfortunate unintended consequences of donors' support, how can we under-stand these ambiguities? Based on an ethnographic study of local Bangladeshi NGOs, the article explores actions and behaviour of grassroots NGO staff. The article shows how, equipped with an ideal image of the altruistic development worker, the staff's encounter with reality provides them with contradictory and confusing messages as to who they should be and how they should act, resulting in disillusion and moral discord. The analysis examines concepts such as altruism, alienation, goal ambiguity, moral selving and moral discord, with an aim to expand our understanding of some moral dilemmas of development practice, its sources and unpredictable outcomes.